2016
DOI: 10.1097/md.0000000000004384
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis and follow-up of chronic active Epstein–Barr-virus-associated cardiovascular complications with cardiovascular magnetic resonance imaging

Abstract: Introduction:Chronic active Epstein–Barr virus (EBV) infection (CAEBV) is characterized as chronic or recurrent mononucleosis-like symptoms and elevated EBV deoxyribonucleic acid (EBV-DNA) copies. Cardiovascular complications have high morbidity and mortality. The treatment regimen for CAEBV has not been established yet, resulting in poor prognoses. Herein, we present a case of cardiovascular magnetic resonance imaging (CMRI) evaluation with a series of sequences for CAEBV-associated cardiovascular involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…After 10 months, the PE did not reoccur and there were no obvious changes in the CAAs. However, CAEBV with cardiovascular complications has been reported in a relatively large number of patients, with the coronary artery disease being the most common complication [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 10 months, the PE did not reoccur and there were no obvious changes in the CAAs. However, CAEBV with cardiovascular complications has been reported in a relatively large number of patients, with the coronary artery disease being the most common complication [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause of pericardial effusion was not explained by pericardiocentesis, possible causes were ruled out with a negative result of interferon- ing amyloidosis. It was reported that cardiovascular magnetic resonance imaging could effectively and comprehensively reveal the early and dynamic changes presenting as aneurysms and stenoses of the coronary arteries, and act as an important tool in the field of cardiovascular complications (10). Unfortunately, the patient was reluctant to perform this noninvasive approach due to economic reasons and decided to give up treatment in the end.…”
Section: Discussionmentioning
confidence: 99%
“…There were 10 (18.5%) adults ( 6 , 12 – 20 ) and 44 (71.5%) children (under 18 years old) ( 7 9 , 21 35 ), ranging in age from 1 year and 5 months to 67 years. In terms of sex, there were 28 male ( 7 , 12 , 16 , 18 , 20 , 23 , 25 , 27 , 28 , 30 – 34 ) and 26 female patients ( 6 , 8 , 9 , 13 , 15 , 17 , 19 , 21 , 22 , 24 , 26 – 29 , 31 , 35 ). Regarding the diagnosis of EBV infection, 23 (42.6%) were diagnosed with AEBV ( 6 , 13 15 , 17 , 18 , 25 , 27 , 32 ), 20 (37.0%) with CAEBV ( 7 , 8 , 16 , 19 22 , 28 – 31 , 34 ), 6 (11.1%) had a complication of CAEBV and HLH ( 12 , 24 , 28 , 31 ), 4 (7.4%) had a diagnosis of EBV-HLH ( 9 , 23 , 33 , 35 ), and 1 (1.9%) had reactivated EBV ( 26 ).…”
Section: Different Cardiovascular Manifestations and Diagnosis In Pat...mentioning
confidence: 99%
“…Of the included patients, 42 (95.5%) were children ( 7 9 , 21 31 , 34 , 35 ) and two (4.5%) were adults ( 12 , 16 ). Regarding gender, 23 (52.3%) were male ( 7 , 8 , 23 , 25 , 27 , 28 , 30 , 31 , 34 ) and 21 (47.7%) were female ( 9 , 12 , 16 , 21 , 22 , 24 , 26 – 29 , 31 , 35 ). Pediatric patients ranged in age from 1 year and 5 months to 16 years.…”
Section: Different Cardiovascular Manifestations and Diagnosis In Pat...mentioning
confidence: 99%
See 1 more Smart Citation